The Role of Religious Counselors in Eradicating Qur'anic Illiteracy: A Case Study in Somba Opu Subdistrict, Gowa Regency - Krismon; Muchtar, M. Ilham; Asdar, A. (JURNAL MAHASISWA YUSTISI, 2025)
This study investigates the role of Islamic religious counselors in eradicating Qur’anic illiteracy in Somba Opu Subdistrict, Gowa Regency. Qur’anic illiteracy remains a significant issue in Indonesia, affecting individuals’ ability to access and practice core Islamic teachings. Utilizing a qualitative descriptive method with a case study approach, the research involved interviews, observation, and documentation to understand the strategies implemented by religious counselors. The findings reveal that counselors play a central role in facilitating Qur’anic literacy programs by providing instruction using structured methods such as Iqra and Al-Barqi, conducting outreach activities, evaluating learner progress, and engaging with community leaders. Supporting factors include strong religious motivation, collaboration with local stakeholders, and institutional backing from the Office of Religious Affairs (KUA). However, challenges such as digital distractions, limited human resources, and low learner motivation continue to hinder program effectiveness. This study highlights the importance of strengthening the role of religious counselors and promoting community-based religious education as a key strategy for addressing Qur’anic illiteracy in Indonesia.